(3QSGdI aj GdehGQjKs - (3YHO Gddg Hf Ndjds ((3MSf Hf Ydi Hf fGUQ GdcQHdGFi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO Med GdYHO GdabjQ YHO Gddg Hf Ndjd GdNHQ GdhGQO Yf QShd Gddg Udi Gddg Ydjg hSde Ydjg hBdg CLeYjf hgh JYdehG GdehGQjK hYdehgG GdfGS s
(3BNQgG (B:s
(3hCeG eYQaI eG jSJMb cd hGQK eY GdEfaQGO hGdELJeGY adjWdH ai eMdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eOQSI GdMLjGJ (B_ (3GdehUd (B(21) s
Keywords: (3GdeLGejYs